Precision Agriculture Technology Innovation in Supporting Food Security in the Era of Industrial Revolution 4.0 - Judijanto, Loso; Wahyuni, Ira; Suryandari, Ratnawati Yuni (Westscience Press, 2024)
The Industrial Revolution 4.0 has driven transformative changes in agriculture through the adoption of precision agriculture (PA) technologies, aimed at optimizing resource use and enhancing food security. This study conducts a systematic literature review of 52 Scopus-indexed documents to evaluate the role of these technologies in addressing global food challenges. Key innovations such as IoT, AI, drones, and robotics are highlighted for their contributions to increasing agricultural productivity, ensuring environmental sustainability, and mitigating the effects of climate variability. Despite their potential, barriers such as high implementation costs, technological complexity, and limited access in developing regions hinder widespread adoption. The findings underscore the need for targeted policies, infrastructure development, and inclusive practices to harness PA technologies for food security fully. This study provides valuable insights for researchers, policymakers, and practitioners to foster sustainable agricultural systems.